Paths to an Innovative, Humane and Sustainable University: The Creation of the Pro-Rectorate of Citizenship and Sustainability at UFMS - Costa, Joao Vitor; de Carvalho, Leonardo Chaves; Queiroz, Vivina Dias Sol; Contrera, Luciana; Itavo, Camila Celeste Brandao Ferreira; de Souza, Albert Schiaveto (Journal of Sustainability Perspectives, 2025)
The establishment of the Pro-Rectorate of Citizenship and Sustainability at the Universidade Federal de Mato Grosso do Sul (Procids/UFMS) marks an innovative milestone in Brazilian university governance, consolidating an institutional model that strategically integrates citizenship and sustainability into higher education. This pioneering initiative underscores UFMS’s commitment to the implementation of the Sustainable Development Goals (SDGs), demonstrating how universities can actively contribute to sustainable development in its multiple dimensions. The Pro-Rectorate consists of the Citizenship Board (Dicid) and the Sustainability Board (Dides), both responsible for coordinating and promoting actions focused on inclusion, diversity, equity, and sustainable institutional management. While Dicid develops and implements affirmative action and human rights policies, fostering a more inclusive and equitable academic environment, Dides oversees and applies sustainable practices, monitors institutional indicators, and ensures UFMS's participation in national and international sustainability rankings. This innovative organizational structure reinforces the role of higher education institutions as active agents in building more sustainable and socially just societies. UFMS strengthens its leadership in sustainability and citizenship, serving as a reference for other institutions by demonstrating that integrating the SDGs into university management generates concrete and lasting impacts in academia and society.